Description of Junior High School Students in Generlizing Patterns Based on Semiotic Perspective - Dewi, Pradnya Paramita; Setyadi, Danang; Mampouw, Helti Lygia (International Journal of Active Learning, 2017)
Generalization is a reasoning in making conclusions that contain symbolism and are general. Semiotics have an important role in the process of generalization, in which generalize the pattern not only seen from the work of students but based on the process of students in understanding and making things. This paper aims to describe how junior high school students generalize patterns based on semiotic perspectives. The type of this research is descriptive qualitative in which data obtained by test, interview and observation. The subjects consist of 3 students of grade VIII junior high school students of 1 high, moderate, and low mathematics students. The findings of this research are at the factual stage the three subjects have the same gesture and word. But in the contextual phase each subject has a different way or step of work in accordance with the understanding possessed by each subject and the last stage of the symbolization of the three subjects can create the same formula. This paper is expected to be used as a reference for teachers to understand the ability of students in the generalization process.